Polysaccharides, Next Potential Agent for the Treatment of Epilepsy? - Xie, Xuemin; Wu, Youliang; Xie, Haitao; Wang, Haiyan; Zhang, Xiaojing; Yu, Jiabin; Zhu, Shaofang; Zhao, Jing; Sui, Lisen; Li, Shaoping (Frontiers in Pharmacology, 2022)
Epilepsy is a chronic neurological disorder. Current pharmacological therapies for epilepsy have limited efficacy that result in refractory epilepsy (RE). Owing to the limitations of conventional therapies, there is a need to develop new anti-epileptic drugs. Studies have shown that some molecule compounds in Traditional Chinese Medicines (TCMs) may be a option and one of them is polysaccharides. The beneficial effects of polysaccharides treating epilepsy include regulation of inflammatory factors, neurotransmitters, ion channels, and antioxidant reactions. Since the human body lacks polysaccharide hydrolase, most polysaccharides cannot be directly digested and absorbed by the human body, which could be digested by intestinal microbial flora. Intestinal microbial flora, referred as “intestinal brain organ” or “adult's second brain”, may be a target for treatment of epilepsy. Therefore, polysaccharides are hypothesized and discussed as potential therapeutic agents of epilepsy in this article.